Peeking and poking at atoms with laser light - Kjærgaard, Niels (New Zealand Science Review, 2015)
​Richard Feynman, in his famous Lectures on Physics, toyed with the idea of all scientific knowledge being wiped out and facing the choice of passing one single idea down to future generations (Feynman et al. 1989). He believed it should be the hypothesis that all things are made of atoms. The idea that matter is built up from discrete fundamental units can be traced back to several ancient cultures (the word atom deriving from the Greek word atomos ‘cannot be divided’). It is only within the last century or so, however, that theories for atomic structure were developed to explain a series of phenomena observed throughout the 18th–19th Centuries. Many of these phenomena were optical, such as Melvill’s observation in 1752 that a mixture of sea salt and alcohol would burn with a yellow flame (see Figure 1) or Wollaston’s observation in 1802 that sunlight contains black lines in its spectrum (Cajori 1962). Further refinement and characterisation from people like Fraunhofer, Kirchoff, Bun-sen, Balmer, and Zeeman followed, but it was not until 1913, with the introduction of the Rutherford-Bohr atomic model, that a cornerstone was laid for what would become a quantum mechanical description of the atom.